Plasma Cell–Rich Viral Myocarditis Identified at Autopsy: A Case Report: Prominent Plasma Cell Infiltration in Fatal Myocarditis Associated with Acute Respiratory Distress Syndrome and Multiorgan Injury - Qavam, Samiramis; Emaminia, Mohamad Saeid; Bakhtiyari, Hanie; Hafezi Ahmadi, Mohamadreza; Bakhtiyari, Amin (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Viral myocarditis is a clinically significant inflammatory disease of the myocardium and a well-established cause of sudden and unexpected death, particularly in young and middle-aged individuals. Histopathological diagnosis at autopsy may be challenging, especially when inflammatory patterns deviate from classic lymphocytic predominance. Case Presentation: We report the case of a 37-year-old man with a known history of chronic heart failure and seizures who presented with generalized weakness and died within 24 hours of hospital admission despite supportive management. A complete medicolegal autopsy with detailed histopathological examination was performed. Microscopic evaluation revealed plasma cell–rich lymphocytic myocarditis, accompanied by pathological findings consistent with acute respiratory distress syndrome (ARDS), including diffuse interstitial edema and inflammatory infiltration of the lungs. Additional findings included mild hepatitis and acute tubular necrosis, indicating multiorgan involvement. Conclusion: The constellation of findings supports death due to fulminant viral myocarditis associated with systemic inflammatory response and secondary ARDS. This case highlights the diagnostic value of meticulous myocardial histopathological assessment, particularly the recognition of plasma cells as supportive evidence of viral myocarditis, and underscores the potential for rapid clinical deterioration and fatal outcome in patients with underlying cardiac disease.